2020
DOI: 10.1136/bmjdrc-2019-000732
|View full text |Cite
|
Sign up to set email alerts
|

Decreased risk of colorectal cancer among patients with type 2 diabetes receiving Chinese herbal medicine: a population-based cohort study

Abstract: ObjectivesPatients with type 2 diabetes have a higher risk of colorectal cancer (CRC), but whether Chinese herbal medicines (CHMs) can reduce this risk is unknown. This study investigated the effect that CHMs have on CRC risk in patients with type 2 diabetes.Research design and methodsThis cohort study used the Taiwanese National Health Insurance Research Database to identify 54 744 patients, newly diagnosed with type 2 diabetes, aged 20–70 years, who were receiving treatment between 1998 and 2007. From this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Our findings are similar to those previous studies. For example, a population-based cohort study revealed a reduced risk of colorectal cancer in patients with T2DM who were treated with TCM, 11 and a case-control study of TCM products showed a decrease in breast cancer risk in women with T2DM. 26 Although the mechanism by which T2DM increases the risk of cancer is still unclear, antidiabetic drugs, such as metformin, are believed to prevent cancer development, and their efficacies have been evaluated in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are similar to those previous studies. For example, a population-based cohort study revealed a reduced risk of colorectal cancer in patients with T2DM who were treated with TCM, 11 and a case-control study of TCM products showed a decrease in breast cancer risk in women with T2DM. 26 Although the mechanism by which T2DM increases the risk of cancer is still unclear, antidiabetic drugs, such as metformin, are believed to prevent cancer development, and their efficacies have been evaluated in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Chronic intestinal inflammation is considered the most important mechanism leading to the pathogenesis of colorectal cancer. 11 , 31 One possible mechanism of TCM in reducing cancer risk is its anti-inflammatory properties. 32 In addition, our study showed that TCM therapy reduced the risk of hospitalization and mortality in diabetic patients with CIS regardless of sex, age, income, catastrophic illness, season, urbanization degree, and hospital level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zheng et al confirmed that LDP can inhibit the metastasis of breast cancer by inhibiting the expression of TCF-1, β-catenin, cyclin-D1 ( 16 ). In addition, LDP can also suppress the development of gastrointestinal tumors ( 17 , 18 ). This study investigated the effect of LDP on TKIs-induced proteinuria and the possible mechanism, and it was demonstrated that both the function and pathological changes of kidneys in mice treated with TKIs were improved after LDP treatment.…”
Section: Introductionmentioning
confidence: 99%
“…AR is currently included in the Pharmacopoeia of China not only as a diuretic but also as a representative hypoglycemic and hypolipidemic traditional Chinese herbal medicine. AR is an important component of many famous Chinese formulas for hypoglycemic from Febrile and Miscellaneous Disease (Shang Han Lun in Chinese) or Synopsis of Golden Chamber, including Zexie docotion, Ba wei shen qi wan, and Liu wei di huang wan [ 5 , 9 , 10 ], for usage as hypoglycemic because of their low toxicity, high effectiveness, and minimal side effects. Our previous studies reported the hypoglycemic activity of the ethanol extract of AR [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%